Obesity-Related Chronic Kidney Disease: Current State of Knowledge - Grabowska, Martyna; Grabowska, Karolina; Kubicka, Jagoda (Quality in Sport, 2026)
Introduction: Obesity and chronic kidney disease are a growing global health problem that often coexist1. Obesity is an independent risk factor for CKD, promoting kidney damage through hemodynamic and metabolic mechanisms2. Aim of the study: This article aims to summarize current evidence on chronic kidney disease in the context of obesity, focusing on key pathophysiological pathways and contemporary strategies for prevention and treatment. Material and methods: A narrative review of the literature was performed using PubMed, Google Scholar, MedRxiv, and Scopus to identify human and selected experimental studies addressing epidemiology, mechanisms, diagnosis, and treatment of obesity-related chronic kidney disease. Summary of current knowledge: Obesity-related CKD arises from interconnected hemodynamic, metabolic, inflammatory, and hormonal mechanisms, leading to hyperfiltration, proteinuria, and progressive renal damage34. The disease is often clinically silent, with albuminuria as an early marker56. Management requires early detection, weight reduction, RAAS blockade, and novel therapies such as SGLT2 inhibitors and GLP-1 receptor agonists, which provide renal protection beyond weight loss alone7. Conclusion: Obesity is an independent driver of chronic kidney disease89. Obesity-related CKD results from hemodynamic and metabolic injury and is often underdiagnosed5. Early detection and modern therapies are key to slowing progression and reducing risk.